Basic research and opportunities for translational advancement in the field of mammalian ∼12-hour ultradian chronobiology - Dion, William; Zhu, Bokai (Frontiers in Physiology, 2024)
Repetitive variations, such as oscillation, are ubiquitous in biology. In this mini review, we present a general summary of the ∼24 h circadian clock and provide a fundamental overview of another biological timekeeper that maintains ∼12 h oscillations. This ∼12 h oscillator is proposed to function independently of the circadian clock to regulate ultradian biological rhythms relevant to both protein homeostasis and liver health. Recent studies exploring these ∼12 h rhythms in humans are discussed, followed by our proposal that mammary gland physiology represents a promising area for further research. We conclude by highlighting potential translational applications in ∼12 h ultradian chronobiology.